ASPECTS OF ENSURING RIGHTS OF PERSONS DURING EXPERT-EXAMINATION IN CRIMINAL PROCEDURE - Sumbarova, Marina (Administrative and Criminal Justice, 2015)
The key issues in this article are related to procedural activity of participants of criminal procedure at investigation of crimes and, in particular, the victim are considered. The separate criminal procedure provisions relating to the legal characteristic of the victim are defined; situations of a legal regulation of appointment and production of examinations are analyzed during pre-judicial criminal trial, the characteristic of the right of acquaintance of participants of criminal trial with the judgment and questions of interaction of the persons directing process with the expert at investigation of crimes. In the conclusion in the context of the designated problems, the author offers recommendations of organizational and tactical character for improvement of interaction of the investigator and the forensic expert at investigation of crimes and, in particular, at purpose of examinations. In the conclusion offers on a being of the executed research on improvement of concrete standards of the criminal procedure law are also formulated.